تقييم طرائق تقدير التبخر-نتح المرجعي اليومي باستخدام حوض التبخر نوع A في الساحل السوري - عمار غطفان; حماد منذر; عباس ماريا (Latakia University Journal -Engineering Sciences Series, 2019)
Evapotranspiration is one of the components of the hydrological cycle. The accurate estimating of evapotranspiration affects the study of water balance, which in turn affects the efficiency of planning and management of water resources. The aim of this study is to evaluate methods for estimating daily reference evapotranspiration in Syrian Coast using pan evaporation class A. There for, seven methods (the formulas were suggested by Ammar and Hammad and Abbas, FAO-24, Cuenca, Snyder, Pereira, and Allen) were evaluated by comparing them results with the result from Penman-Monteith equation (FAO-56). The daily metrological data for the 16 Tishreen-dam and Al-Basil stations were used for assessment for the period from 2007 to 2013. The statistical criteria used for the assessment are: correlation coefficient (R), coefficient of determination ( ), mean absolute error ( ), root mean square error ( ), index of agreement( ), performance index ( ). the study showed that the equation proposed by Ammar, Hammad and Abbas, which its inputs pan evaporation and extraterrestrial radiation, is the best for estimating daily reference evapotranspiration in Syrian Coast, with high agreement D (0.96), performance index C (0.89), RMSE (0.64mm / day) and R (0.925). Therefore, it is recommended to use this method to estimate daily reference evapotranspiration in Syrian coast, instead of complex equations which need information for many climatic elements that may be missing and unavailable. يعتبر التبخر-نتح أحد مكونات الدورة الهيدرولوجية, ويؤثر التقدير الدقيق للتبخر-نتح في دراسة الموازنة المائية التي تؤثر بدورها على كفاءة التخطيط وإدارة الموارد المائية. يهدف هذا البحث إلى تقييم الطرائق المستخدمة في تقدير التبخر-نتح المرجعي اليومي باستخدام حوض التبخر نوع A في الساحل السوري. من أجل ذلك تم تقييم سبع طرائق متمثلةً بـ (المعادلتين المقترحتين من قِبل عمار وحماد وعباس, جداولFAO-24, معادلة Cuenca, Snyder, Pereira, وAllen), وذلك من خلال مقارنة النتائج مع نتائج معادلة بنمان- مونتيث الموصى بها من قبل منظمة الأغذية والزراعة العالمية (FAO-56). وقد استخدمت للتقييم البيانات اليومية المناخية لمحطتي سد 16 تشرين وسد الباسل للفترة الممتدة من 2007 إلى 2013. وكانت المعايير الإحصائية المستخدمة: معامل الارتباط ( ), معامل التحديد ( ), معدل الخطأ المطلق ( ), جذر متوسط مربع الخطأ ( ), معامل التوافق ( ) ومعامل الأداء ( ). بينت الدراسة أن المعادلة المقترحة من قِبل عمار وحماد وعباس, والتي مدخلاتها التبخر الإنائي والإشعاع الشمسي الواصل إلى الغلاف الجوي الخارجي، هي الأفضل لتقدير التبخر-نتح المرجعي اليومي في الساحل السوري، بتوافق عالي )) (0.96) وأداء ممتاز )) (0.89), حيث بلغت قيمة ( ) وقيمة (0.925). لذلك يوصى باستخدامها لتقدير التبخر-نتح المرجعي اليومي في الساحل السوري بدلاً من معادلات معقدة تحتاج معلومات لعناصر مناخية كثيرة قد تكون مفقودة وغير متوفرة.